2015
DOI: 10.1038/ncomms9520
|View full text |Cite
|
Sign up to set email alerts
|

ATP binding to neighbouring subunits and intersubunit allosteric coupling underlie proteasomal ATPase function

Abstract: The primary functions of the proteasome are driven by a highly allosteric ATPase complex. ATP-binding to only two subunits in this hexameric complex triggers substrate binding, ATPase-20S association, and 20S gate-opening. However, it is unclear how ATP-binding and hydrolysis spatially and temporally coordinates these allosteric effects to drive substrate translocation into the 20S. Here, we use FRET to show that the proteasomal ATPases from eukaryotes (RPTs) and archaea (PAN) bind ATP with high affinity at ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
49
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 55 publications
17
49
2
Order By: Relevance
“…3). Interestingly, the half-life of native, monomeric GFP found here (~1 min 45 s) is comparable to the time based on biochemical assays of ATP consumption rates of different ATPase systems who found that several hundred ATP molecules are needed to unfold one GFPssrA at hydrolyses rates of a few ATP per second1031.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…3). Interestingly, the half-life of native, monomeric GFP found here (~1 min 45 s) is comparable to the time based on biochemical assays of ATP consumption rates of different ATPase systems who found that several hundred ATP molecules are needed to unfold one GFPssrA at hydrolyses rates of a few ATP per second1031.…”
Section: Discussionsupporting
confidence: 77%
“…In the case of proteolytical AAA ATPases, ATP-binding and -hydrolysis fuel changes in the conformation of the rings which cause movements of the axial pore loops implicated in substrate translocation and unfolding89. Despite the central importance of the nucleotide-dependent, coordinated conformational changes in AAA+ proteolytical unfoldases, and while progress has been obtained recently on the sequential order of nucleotide binding and hydrolysis10, little is known on the potential coordination of these events with the time course of substrate unfolding and release11.…”
mentioning
confidence: 99%
“…Such a configuration is consistent with a proposed rotary hydrolysis mechanism [8,9] in which ATP hydrolysis takes place in coordinated waves counterclockwise around the ring. However, it is at odds with nucleotide binding configurations known for other AAA+ family ATPases that unfold proteins, such as the bacterial ClpX [10].…”
supporting
confidence: 88%
“…Arginine fingers are known to sense nucleotide bound by adjacent subunits in the ATPase ring [11], but the arrangement of nucleotide counterclockwise to Rpt2 raises the intriguing possibility that they could contribute directly to catalysis [9]. Namely, protrusion of the Rpt2 arginine fingers into the Rpt1 nucleotide pocket may be necessary to stimulate ATP binding or hydrolysis by Rpt1, implicating Rpt1 as the initiator of ATP hydrolysis around the ring [8].…”
mentioning
confidence: 99%
“…The mechanism by which ATPase activity is restrained until completion of base assembly is unknown, but likely depends upon critical interactions of the ATPase subunits with neighboring ATPases to orient nucleotide properly for catalysis (Kim et al 2015), which would serve to couple completion of the ATPase ring to maturation of ATPase activity. The fully assembled base contains ubiquitin receptors and unfolding activity, even in the absence of the lid and CP.…”
Section: Maturation Of Rp Enzymatic Activitiesmentioning
confidence: 99%